The Influence of Transfer Pricing and Management Compensation Toward Tax Avoidance of Food and Beverage Companies Listed on the Indonesia Stock Exchange - Tarigan, Louis Yosen Primsa (Jurnal Penelitian Akuntansi (JPA), 2024)
Food and beverage industry has been a major player in Indonesia economic, constituting up to 6% of Indonesia GDP. This lead companies involved in the sector to expand from national to multinational companies. In the previous research, transfer pricing and CEO compensation were observed partially in relation to the tax aggressiveness while this research focuses on transfer pricing and management compensation partially and simultaneously toward the tax avoidance.The purpose of this research is to observe the influence of transfer pricing and management compensation toward tax avoidance of food and beverage companies listed on Indonesia Stock Exchange (IDX) from 2020 to 2022. There are two independent variables used in this research, such as transfer pricing and management compensation. The dependent variable of this research is tax avoidance. There are 12 samples out of 122 companies that were chosen in this quantitative research utilizing purposive sampling technique and secondary data collection method.The result of this research shows that transfer pricing has a non-significant influence towards tax avoidance and management compensation has a non-significant influence towards tax avoidance. Furthermore, transfer pricing and management compensation simultaneously have a significant influence towards tax avoidance. Keywords: Tax Avoidance, Transfer Pricing, Management Compensation